The Role of Taklim Assembly for Creating Education Character in Early Childhood - Bahagia, Bahagia; Muniroh, Leni; Halim, Abdul Karim; Ritzkal, Ritzkal; Wibowo, Rimun; Al-Wahid, M. Azhar; Noor, Zakky Muhammad (Universitas Pahlawan Tuanku Tambusai, 2022)
The Majlis Ta’lim is classified as non-formal education that is close to the community and discusses issues related to the community. The purpose of this study is to find the transfer of moral education values to children through parents who participate in The Majlis Ta’lim. This research is descriptive qualitative research. While the sampling method includes using a purposive technique. Meanwhile, data collection was carried out in various ways including observation, documentation, and in-dept-interview. The results showed that the Majlis Ta’lim plays an important role in shaping children's morals by providing material to parents in the mosque and the prayer room. The material transfer is carried out to parents and parents will later transfer material to children at home in the form of behavior. The material provided includes material on maintaining oral behavior with parents. The material that has been obtained will be practiced at home so that children will see and observe this behavior. Another way is material about social life, including the urgency of friendship with neighbors so that parents practice it by bringing their children directly to their neighbor’s house. Habituation like this will make children behave socially toward neighbors. Finally, the habit of praying to children, here The Majlis Ta’lim will provide material about prayers in everyday life to parents so that parents will implement them at home.